Frank zappa e il ’68 tedesco. Un paradosso transatlantico e un’accusa di provincialismo culturale = Frank Zappa, Germany, 1968. A transatlantic paradox and an accusation of cultural provincialism - Gianfranco Salvatore (H-ermes: Journal of Communication, 2018)
FRANK ZAPPA, GERMANY, 1968. A transatlantic paradox and an accusation of cultural provincialism. Besides his autobiography, the rock guitarist and contemporary composer Frank Zappa (1940-1993) has disseminated his thinking through hundreds of highly articulate and seldom repetitive interviews. Published around the world by the international press since 1965, for almost thirty years, his statements, reflections, and analyses display a musicological, sociological, even semiotic and political approach not only to the arts, but to reality in the wider sense. Part of a broader research on his thinking, this paper aims to retrace Zappa’s position towards the protest movement in late Sixties, not only in the USA but also in Europe. A key moment in the development of such position came when he played in West Berlin in 1968 with his band The Mothers of Invention. That concert provides a very good example of a cultural clash between the highly politicized German audience, with its believes and principles, and Zappa’s personal visions for society and the way to improve it. That night the musician realized that ideas and actions implemented by the student protest in Europe, and above all in Germany, were the byproduct of a ‘cultural periphery’ in the worst sense: a sort of provincial extension of the USA which had been culturally colonized by the American model of the ‘youth revolt’, with local distortions and worsening. The crucial evolution of politics in the late Sixties both in Germany and in the USA, the social theories on youth developed during the Fifties and the Sixties, the influence and impact of Zappa’s songs and lyrics during the late Sixties, and the reaction of European media to his statements, are here examined contextually to the unfortunate concert in Berlin and the evolution of Zappa’s sociological and political theories developed after that controversial episode.